Distribución de Ecteinascidiaturbinata (Asddiacea: Pemphoridae) en los manglares de la Península de Yucatán, México - CarbaUo, Jorge Luis (Revista de Biología Tropical, 2000)
The ascidian Ecteinascidia turbinata synthesizes sorne of the most promising substances against solid-type tumors, but the only available source are the natural populations of this tunicate, which is reared or collected in different parts of the world. A total of 33 locations were sampled in the Gulf of Mexico and· rhe Yucatan Peninsula. T he tunicate was not found in Veracruz, Tabasco and Campeche, but it was weH established on mangrove roots in the Yucatan PerlÍnsula where we estimated densitits more or less equal to oue colony and an average production of 1]5 g of bíomass per lineal meter of mangrove coastline in oae location (Río Lagartos). Sustaínable management appears to be possible.